Book review: Ravinder Kaur and Rajni Palriwala, Marrying in South Asia: Shifting Concepts, Changing Practices in a Globalising World. (February 2019) - Bhandari, Parul
Ravinder Kaur and Rajni Palriwala, Marrying in South Asia: Shifting Concepts, Changing Practices in a Globalising World . New Delhi: Orient Blackswan, 2013, 420 pages, ₹925. ISBN: 978-81-250-5355-2.